Carbon-based nanostructured composite films : elastic, mechanical and optoelectronic properties derived from computer simulations - Fyta, Maria G.; Kelires, Pantelis C.; Mathioudakis, Christos (My University, 2011)
In this review, we present our recent computational work on carbon-based nanostructured composites. These materials consist of carbon crystallites embedded in an amorphous carbon matrix and are modeled here through classical and semi-empirical quantum-mechanical simulations. We investigate the energetics, mechano-elastic, and optoelectronic properties of these materials. Once the stability of the composites is discussed, we move on to the calculation of their elastic moduli and constants, their anisotropy and elastic recovery. At a next step, we focus on diamond composites, which were found to be the most stable among the composites studied, and went beyond the elastic regime to investigate their ideal fracture. Finally, for these materials, the electronic density of states, dielectric function, and optical response were calculated and linked to the disorder in the structures. Our findings unveil the high potential of these materials in nanotechnological applications, especially as ultra-hard coatings.
Keywords: Nanotubes; Optoelectronic properties; Carbon nanocomposites; Amorphous carbon; Mechanical properties; peer reviewed